“SO STONED”: Common Sense Approach of the Dizzy Patient - Wuyts, Floris L.; Van Rompaey, Vincent; Maes, Leen K. (Frontiers in Surgery, 2016)
The history taking of a dizzy patient is of utmost importance in order to differentiate the possible aetiologies of vertigo. The key factors that allow a first approximation of diagnosis identification are based on the time profile, symptom profile and trigger profile of the disease. The here proposed mnemonic “SO STONED” comprises eight different dimensions that characterise the vertigo-related complaints of the patient and guide the clinician in his or her decision scheme. All the letters “SO STONED” have a specific meaning: Symptoms, Often (Frequency), Since, Trigger, Otology, Neurology, Evolution, Duration. Since the most common vestibular diseases have different fingerprints when all dimensions are considered, this tool can facilitate the identification of the appropriate vestibular diagnosis.